Kecenderungan Mahasiswa Biologi Menggunakan Bahasa Dialeg Daerah Dalam Sehari-Hari - Brema Pratama; Juli Nola Olivia; Rizki Fatahillah Hutasuhut; M Surip (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the tendency of Biology students of Medan State University to use local dialects, particularly Batak and Javanese dialects, in their daily communication. The methods used were interviews and focus group discussions (FGDs) to collect data regarding students' social interactions and how they combine Indonesian with local dialects. The results showed that most students bring their local dialects to the university, which creates a strong cultural identity. Students from outside Medan also tend to adjust to the Medan dialect, but dialect differences often cause difficulties in communication with individuals from different linguistic backgrounds. This research emphasizes the importance of Indonesian as a unifying language that can enhance communication effectiveness in diverse academic environments. By understanding the dynamics of dialect usage, it is hoped to increase awareness of cultural and linguistic diversity in Indonesia.